Risiko Usaha dan Rentabilitas pada BPR Konvensional di Nusa Tenggara Barat - Ni Nyoman Yuliati; I Nengah Arsana; I Made Suardana (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
The purpose of this study was to determine the effect of business risk variables consisting of credit risk, liquidity risk and assets risk on profitability which is proxied by income to total assets on Conventional Rural Banking in Nusa Tenggara Barat (NTB). The population in this study were all conventional rural bank in NTB, totalling 29 banks. The sample was determined by using saturated sampling method so that the entire population of 29 banks was used as the sample. The results of this study indicate that credit risk has a negative relationship and has no significant effect on profitability, liquidity risk has a negative relationship and has a significant effect on profitability and assets risk has a positive relationship and has a significant effect on profitability